Gendered Barriers to Female Academics’ Managerial Advancement in TVET Colleges - Berington Zanoxolo Gobingca (Universitas Nurul Jadid, 2026)
This study aimed to examine factors influencing female academics’ access to managerial positions in TVET colleges. Women remain underrepresented in college leadership despite constitutional and policy commitments to gender equality. Existing studies offer limited insight into how stereotypes, institutional practices, professional relationships, and policy implementation interact within TVET institutions. The study used a qualitative multiple-case design within an interpretivist paradigm. Data were collected through semi-structured interviews with five purposively selected lecturers and analyzed thematically alongside observations. First, participants associated leadership competence and authority more strongly with men than women. Male leadership was therefore treated as the institutional norm. Second, masculine leadership expectations contributed to self-doubt, fear of failure, and some women's reluctance to pursue promotion. These responses reflected socially produced barriers rather than incapacity. Third, limited solidarity among women and preferences for male leaders weakened peer endorsement, mentoring, sponsorship, and legitimacy for female leadership. Together, these mechanisms formed a self-reinforcing cycle sustaining male managerial dominance. The study implies that confidence-building alone is insufficient. TVET colleges should strengthen transparent promotion processes, mentoring, sponsorship, selection panels, and equity accountability.